2021
DOI: 10.2147/cmar.s297765
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-MTA1-SMAD7-SMAD3-SOX4-EZH2 Signaling Axis Promotes Viability, Migration, Invasion and EMT of Hepatocellular Carcinoma Cells

Abstract: Introduction Enhancer of zeste homolog 2 (EZH2) is implicated in hepatocellular carcinoma (HCC), but whether transforming growth factor-β (TGF-β)-metastasis associated 1 (MTA1)-SMAD7-SMAD3-SRY-Box Transcription Factor 4 (SOX4)-EZH2 signaling axis, in which EZH2 participates, is also involved in HCC remained unknown. Methods Data on EZH2 expression in liver hepatocellular carcinoma (LIHC) and its relation with prognosis of HCC patients were predicted and analyzed using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…TGF-β promotes tumor migration and invasion through EMT (24,25). The effect of FXR1 on the TGF-β-induced migration and invasion in HCC cells was thus next assessed.…”
Section: F X R1 Promotes Slug/n-cadherin Expression a Nd Tgf-β-induce...mentioning
confidence: 99%
“…TGF-β promotes tumor migration and invasion through EMT (24,25). The effect of FXR1 on the TGF-β-induced migration and invasion in HCC cells was thus next assessed.…”
Section: F X R1 Promotes Slug/n-cadherin Expression a Nd Tgf-β-induce...mentioning
confidence: 99%
“…Upregulation of EZH2 expression in HCC is associated with unfavorable prognosis. The silence of EZH2 inhibits the HCC cell survival, migration and invasion, increased E-cadherin expression, and decreased N-cadherin and vimentin expression ( Zhang et al, 2021 ). Cell division cycle associated 8 (CDCA8) is an essential component of the chromosome passenger complex (CPC).…”
Section: Discussionmentioning
confidence: 99%
“…Research has also reported that decreased levels of CYP2C9 in HCC tissues [ 50 , 51 ], indicating the involvement of CYP2C9 in detoxification, may play an important role in the initiation of HCC. There is evidence that EZH2 is elevated in HCC and promotes proliferation, migration, and invasion of HCC cells, acted as a negative prognostic biomarker associated with immunosuppression, and is associated with sorafenib resistance in HCC [ 52 , 53 , 54 , 55 ]. SRXN1 , an antioxidant molecule, was significantly upregulated in HCC and its increasement might lessen BTG2 expression, resulting in an increase in HCC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%